In-office Endonasal Minor Revision Rhinoplasty - Auger, Samuel R.; Shah, Anil R. (Facial Plastic Surgery, 2021)
The revision rhinoplasty presents many unique challenges to the facial plastic surgeon. While many cases will require a full revision in the operating room, there are several isolated deformities which may be repaired in the office via an endonasal approach. This provides many benefits to the patient and surgeon including decreased cost, shorter recovery time, avoidance of general anesthesia, and less discomfort. It is critical to identify defects appropriate for endonasal repair, establish clear expectations with the patient, and work within one's skill set and level of experience. The surgeon who can comfortably navigate both open and endonasal techniques can offer their patients a comprehensive set of solutions for revision rhinoplasty. In this article we outline the defects amenable to this type of repair as well as technical considerations for each defect addressed. We hope it serves as a useful framework for the range of deformities the rhinoplasty surgeon may take on for in-office repair.
Keywords: revision rhinoplasty; in-office procedure; facial plastic surgery; endonasal rhinoplasty